Real Estate and Stating the Real in Jean Echenoz's L'Occupation des sols - Philip G. Hadlock (Studies in 20th & 21st Century Literature, 2006)
Through its extremely minimal account of the aftermath of an apartment fire, Jean Echenoz's L'Occupation des sols raises intriguing questions about the grounding of property—its occupation des sols—in Western consciousness. The narrative situation allegorizes the longstanding convention in which man is associated with property ownership while woman is associated with property itself. Though seeming to uphold this paradigm, Echenoz presents a challenging perspective of the functions that gendered scenarios of property perform in sustaining symbolic relations and anchoring the "real" in Western thought.
Keywords: apartment fire; apartment; fire; allegories; men; property; women; property ownership; Jean Echenoz; L' Occupation des sols; grounding of property; owning property; Western consciousness; perform; gendered; gender; symbol; western thought